Enzymatic extraction of steviolglycosides in blackberry juice (Rubus adenotrichus) - Gonzalez Torrivilla, Cesar Castor; Perez Sira, Elevina (Revista Colombiana de Investigaciones Agroindustriales, 2017)
The goals of the study were to evaluate yield of the blackberry juice preparation, and at same time of the extraction of sweetener glycosides from dehydrated stevia leaves (Stevia rebaudiana Bertoni), by using enzymatic preparations. Five enzyme preparations were evaluated during the preparation of the sweetener with these glycosides. Two levels of the variables studied were evaluated: enzyme concentration (100 and 200ppm), and incubation period (15 30min), and using two extraction solvents at two temperatures: water and blackberry juice (at 50 and 35 °C, respectively). Efficiency and yield was analyzed by determining suspended insoluble solids (SIS), soluble solids (SS), and quantitation by cromatografía líquida de alta eficacia o High Performance Liquid Chromatography (HPLC) of the main esteviolglucósidos (stevioside and rebaudioside A). Statistical analysis data shown that the incubation time and the enzyme concentration in the enzyme complex did not affect total soluble solids values, but it does in the concentration of SIS, when using the commercial preparation Pectinex Ultra AFPL, as compared with the rest of the tested samples. Similarly, it is shown statistically significant differences in assessing the enzyme-time binomial, in the steviolglycosides extraction in water and blackberry juice. A high concentration of stevioside and rebaudioside A were achieved when using Pectinex Clear, at a concentration of 200 ppm during 30 seconds. However, the obtained values are similar to concentrations quantified in the control sample showing a slight influence of enzymes in the extraction of both steviolglycosides. This result corroborates that the diffusion of these compounds from the leaves to the medium, occurs primarily by the solubility thereof, rather than by hydrolysis caused by specific enzymes used in the study.